On the strongly damped wave equation and the heat equation with mixed boundary conditions - Aloisio F. Neves (Abstract and Applied Analysis)
We study two one-dimensional equations: the strongly damped wave equation and the heat equation, both with mixed boundary conditions. We prove the existence of global strong solutions and the existence of compact global attractors for these equations in two different spaces.